2009
DOI: 10.4278/ajhp.080930-quan-224
|View full text |Cite
|
Sign up to set email alerts
|

The Stratification of Foods on the Basis of Overall Nutritional Quality: The Overall Nutritional Quality Index

Abstract: The ONQI is a sophisticated nutrition guidance system developed by a multidisciplinary group independently of all food industry interests with excellent initial performance in both consumer research and validation testing. Combined with a consumer education program, the ONQI has considerable potential to improve dietary patterns, and consequently the public health. Prospective study of effects on dietary patterns and health outcomes is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 18 publications
0
73
0
Order By: Relevance
“…Katz et al found that approximately 80 % of participants in one study (n 804) reported the ONQI would influence their purchase intentions. While there is a strong correlation between various food products' ONQI scores and the products' nutritional rankings according to expert panellists (36) , the actual algorithm used as the basis for the labelling system has not been released to the public for evaluation.…”
Section: Which Front-of-package Labels Impact Food Consumption?mentioning
confidence: 99%
“…Katz et al found that approximately 80 % of participants in one study (n 804) reported the ONQI would influence their purchase intentions. While there is a strong correlation between various food products' ONQI scores and the products' nutritional rankings according to expert panellists (36) , the actual algorithm used as the basis for the labelling system has not been released to the public for evaluation.…”
Section: Which Front-of-package Labels Impact Food Consumption?mentioning
confidence: 99%
“…Understandably, a consumer education programme will be needed to demonstrate how to use the nutrient density measure within the concept of the total diet. Katz et al (7,10) and Glanz et al (73) showed that using the Nutrient Rich Foods approach was effective in improving the diet of consumers. Larger and longer studies are needed to confirm the findings once a consensus has been reached on whether a nutrient dense score should be developed and validated for single foods or more broadly for assessing nutrient density of the total diet (71) .…”
Section: Practical Implications and Conclusionmentioning
confidence: 99%
“…The algorithms used to profile foods generate a numerical score which can then be used to help consumers make healthier choices (3)(4)(5)(6)(7) , influence regulatory issues (8,9) , help consumers rate foods using front-of-package labels or labels on store shelves (10,11) , define healthy foods that can be advertised to children (12)(13)(14)(15) and motivate industry to develop more healthful foods (15) . Table 1 shows a sample of the variety of nutrient density algorithms that have been used.…”
mentioning
confidence: 99%
“…In addition, the ONQI algorithm considers how nutrients in foods contribute to meeting recommended daily nutrient intakes by including a trajectory score. It is computed by dividing the nutrient quantity per total kilojoules per food serving by the recommended nutrient quantity per total kilojoule intake per day (14) . Healthy nutrients, such as fibre, folate, vitamins A, C, D, E, B 12 and B 6 , potassium, calcium, zinc, n-3 fatty acids, total bioflavonoids, total carotenoids, magnesium and iron, are placed in the numerator, where higher values will raise the NuVal score.…”
Section: Nuval Scoringmentioning
confidence: 99%
“…The NuVal score measures the nutritional quality of thousands of foods on a scale from 1 to 100, with 100 being the most nutritious. It was developed by a panel of twelve scientific experts in various disciplines, including nutritional biochemistry, cardiovascular and cancer epidemiology, weight management, behaviour modification and dietary counselling (14) . Moreover, a scientific advisory board convenes biannually to reauthorize or to update the algorithm to reflect changes in nutrition science and epidemiology.…”
Section: Nuval Scoringmentioning
confidence: 99%